Influence of MWCNT/surfactant dispersions on the rheology of Portland cement pastes (2018)
This work studies the effect of MWCNT/surfactant aqueous dispersions on the rheology of cement paste. Three types of surfactants (sodium dodecyl sulfate, cetylpyridinium chloride and triton TX-100) were used to prepare cement pastes with and without MWCNT. Three rheological parameters were determined for each sample: static yield stress, yield stress, and viscosity. The first was measured directly, while the other two were obtained by fitting a Bingham model to the descending portion of a flow curve. Additionally, X-ray diffraction and isothermal calorimetry were used to follow the hydration reaction of cement during the first hour. It was found that the MWCNT/surfactant dispersions generate an overall shift to higher yield stress values while maintaining viscosity, suggesting a modification of the interparticle attraction. It was concluded that the triple interaction MWCNT-surfactant-cement governs the rheology of cement pastes. © 2018 Elsevier Ltd